Crux [large type] - Tallent, Gabriel (Random House Large Print, 2026)
"Dan and Tamma are two teenagers in their last year of high school in the southern Mojave Desert. One is a gifted golden child, the other a mouthy burnout. Climbing boulders in trash-strewn parking lots during cold desert nights, they seal their unique bond and dream of a life of adventure.As the year progresses and adult reality looms, they are rocked by change and pulled apart by irreconcilable obligations. Differences of class, talent, and prospects take on new importance; options dwindle, and their decisions grow ever more consequential and perilous. It feels inevitable, finally, that something must give.." -Publisher.